"Ajarin" mobile: A mobile technology-based learning application to improve students' mathematical understanding - Deswita, Hera; Japar, Muhammad; Solihatin, Etin (Jurnal Infinity, 2025)
Several previous studies have tried to develop mathematics learning applications, but they are still limited as a learning medium. Developing a digital-based mathematics learning application that facilitates learning from start to finish is necessary. This study aims to develop a viable and effective mobile application. The Development Process uses the CAI design model, which includes needs assessment, design, and development & implementation. Formative evaluations were obtained from expert reviews and students. The experts involved are experts in content, learning media, and multimedia. The formative evaluation stage by students includes one-to-one trials, small groups, and field trials. Research data was collected through questionnaires and test questions. This study involved 1 teacher and 52 high school students in Indonesia. The average score of expert reviews is 3.6, which is in the category of very good. The average score obtained from Formative Evaluation by students is 3.5, with an excellent category. The pretest and post-test scores showed an increase of 40% in students who achieved the completeness of learning outcomes. The average score of N-gain is 0.4 in the medium category. The Ajarin Mobile Application is feasible and effective in improving students' mathematics learning outcomes. This research is expected to be an alternative digital learning resource that makes it easier for teachers to facilitate mathematics learning in schools.